PENGEMBANGAN APLIKASI AUGMENTED REALITY GAMELAN JAWA MENGGUNAKAN METODE MULTIMEDIA DEVELOPMENT LIFE CYCLE - Ardiansyah, Yusuf; Sutarman, Sutarman (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2023)
Javanese Gamelan is a traditional Indonesian musical instrument rich in history and culture. However, many people need to become more familiar with Javanese Gamelan musical instruments and help them understand how to play them. This research aims to increase the general public's interest in studying gamelan by applying augmented reality technology to Android mobile devices. The application is designed to display 3D objects and information about each Javanese gamelan instrument that can be sounded or played. The system design uses the Multimedia Development Life Cycle (MDLC) method. It is implemented using the Marker Tracking method or pattern recognition and marker detection to virtually display 3D models of Javanese Gamelan musical instruments on Android devices. The evaluation was carried out to measure the effectiveness of the application in introducing and educating users about Javanese Gamelan musical instruments. Hopefully, this application for introducing Javanese Gamelan using AR technology can increase people's understanding and appreciation of Javanese Gamelan musical instruments. Apart from that, it is also hoped that this application can become a means of education and promotion of Javanese Gamelan music culture to the younger generation and the wider community.